Effect of applying nursing-based cognitive defusion techniques on mindful awareness, cognitive fusion, and believability of delusions among clients with schizophrenia: a randomized control trial - Ayman Mohamed El-Ashry; Eman Sameh Abd Elhay; Samah Mohamed Taha; Mahmoud Abdelwahab Khedr; Feby Saad Attalla Mansour; Amany Anwar Saeed Alabdullah; Sally Mohammed Farghaly Abdelaliem; Mona Metwally El-Sayed (Frontiers in Psychiatry, 2024)
BackgroundApplying cognitive defusion techniques to enduring psychotic symptoms, such as delusions, presents both a challenge and a promising opportunity for psychiatric nurses to manage delusions among schizophrenia clients.ObjectiveThis study aimed to examine the impact of cognitive defusion techniques on psychological flexibility, mindful awareness, cognitive fusion, and the believability of delusions in schizophrenia clients.MethodologyThis study used a single-blind, parallel-arm Randomized Controlled Trial design. Over five weeks, 70 clients with schizophrenia were randomized to either the cognitive defusion intervention group (n = 35) or the control group (n = 35).FindingsThe participants showed significant reductions in the believability of delusions, cognitive fusion, and psychological inflexibility immediately after the intervention and at follow-up. Notable enhancements were observed in cognitive defusion and mindfulness awareness abilities.ConclusionCognitive defusion techniques positively affect schizophrenia clients who struggle with persistent delusional beliefs. This underscores the importance of further investigating this approach to decrease the intensity of delusions as part of a comprehensive therapeutic intervention. Psychiatric nurses must receive training in “cognitive defusion skills” to aid schizophrenia clients in becoming more aware of their emotions and modifying their coping strategies for delusional beliefs. On August 3, 2023, the research was retrospectively registered under the reference number NCT05759091 as a randomized clinical trial.Clinical trial registrationhttps://classic.clinicaltrials.gov/ct2/show/NCT05759091, identifier NCT05759091.